SNP genotypes (ZIP) - Malenfant, René; Davis, Corey; Richardson, Evan; Lunn, Nicholas; Coltman, David (Dryad Digital Repository, 2018)
Raw SNP genotypes in PLINK format (i.e., .ped & .map file) before quality-control filtering.